Metal-free direct thiolation of terminal alkynes with methyl sulfoxides. (12th January 2023) - Chen, Chen; Pan, Liangliang; Zhu, Jinchen; Shao, Junfa; Dai, Jiaming; Qian, Guoying; Rong, Zhouting
Graphical abstract: Abstract: A metal-free method has been developed for the direct thiolation of terminal alkynes with methyl sulfoxides, which affords various alkynyl sulfides. This transformation features excellent functional group tolerance, good stability in large-scale preparation and atom economy, which makes this reaction a practical method for the synthesis of alkynyl sulfides.